Lower Eocene Crustacean Burrows (Israel) Reflect a Change from K- to r-Type Mode of Breeding Across the K-T Boundary Clarifying the Process of the End-Cretaceous Biological Crisis - Lewy, Zeev; Dvorachek, Michael; Perelis-Grossowicz, Lydia; Ilani, Shimon (IntechOpen, 2011)
None